Expanding family planning options: offering the standard, days Method (TM) to women in Istanbul - (:unkn) unknown (BMJ PUBLISHING GROUP, 2005)
Background This study introduced the Standard Days Method (TM) (SDM), a fertility awareness-based method of family planning, to couples in a region of Istanbul, Turkey who were using a method of low effectiveness or no family planning method. The objective was to determine potential demand for, and satisfaction with, the SDM. Methods A total of 657 couples were selected by systematic sampling and offered the SDM. Those accepting this method were interviewed 1 and 3 months after starting the SDM. Results Some 47% of the participants were satisfied with the method and intended to continue using it. Conclusions Potential demand for the SDM was 80.3% (278/346 eligible women) among couples who were using a method of low effectiveness or no family planning method. Our results suggest that adding the SDM to the contraceptive method mix may benefit Turkish women.